Last Chance for Life: Clemency in Southeast Asian Death Penalty Cases 2019
DOI: 10.1093/oso/9780198809715.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Four Models of Clemency

Abstract: Chapter 2 provides the theoretical framework for a comparative study of clemency in death penalty cases. It begins by clarifying the terminology used throughout the book, including the local terms used in Southeast Asian legal systems for executive ‘clemency’. Then, drawing in particular from the work of Douglas Hay et al (1975), Leslie Sebba (1977a; 1977b); Kathleen Dean Moore (1989), Daniel Kobil (1991; 2003; 2007), Elizabeth Rapaport (1998–2000; 2001), and Austin Sarat (2005; 2008), Chapter 2 suggests four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…At a time of punitiveness, rather than reinventing the wheel, presidents have continued to offer established justifications to validate clemency grants. While some evidence indicates that a retributivists conception prevails in the recent practice of clemency (Sarat, 2005), this study found, similarly to Pascoe (2019), that none of the administrations fit with one of the three rationales of clemency. Statements often draw from multiple rationales at the same time and reveal significant variation in how clemency follows such logics.…”
Section: Justifying Clemency In a Punitive Erasupporting
confidence: 50%
See 4 more Smart Citations
“…At a time of punitiveness, rather than reinventing the wheel, presidents have continued to offer established justifications to validate clemency grants. While some evidence indicates that a retributivists conception prevails in the recent practice of clemency (Sarat, 2005), this study found, similarly to Pascoe (2019), that none of the administrations fit with one of the three rationales of clemency. Statements often draw from multiple rationales at the same time and reveal significant variation in how clemency follows such logics.…”
Section: Justifying Clemency In a Punitive Erasupporting
confidence: 50%
“…Legal theorists have explored the development, organization and practice of clemency in a comparative perspective in modern common-law democracies (Novak, 2016). This research found that clemency performs three main functions: redemption, utilitarianism, and retributivism (Pascoe, 2019). Clemency as redemption is granted in light of individuals’ character and commendable behaviour.…”
Section: The Literature On Executive Clemencymentioning
confidence: 98%
See 3 more Smart Citations